KONSEP HUSN AL-KHULUQ MENURUT AL-GHAZALI DAN RELEVANSINYA TERHADAP SIKAP MODERASI BERAGAMA - Abdul Ghofur (Academic Journal of Islamic Principles and Philosophy, 2022)
This study aims to find out the concept of “husn khuluq” according to Al-Ghazali in the book of Ihya' Ulumuddin and see its relevance to the concept of “religious moderation.” This study is conducted using the library research method by collecting and analyzing all aspects related to the theme. This article shows that the concept of husn al-khuluq requires a person’s inner aspect. The concept of religious moderation and the concept of husn al-khuluq have the same emphasis, namely al-i’tidal (fair, in the middle). Someone who has husn al-khuluq is already moderate. According to al-Ghazali, there are at least four important points that become substantial basics that form good morals (husn al-khuluq), namely al-Hikmah, ash-Syaja’ah, al-Iffah, and al-‘Adlu. Some of these things, if done with full confidence, can form a strong character for a person in their religious moderation.